Computational Approaches: Drug Discovery and Design in Medicinal Chemistry and Bioinformatics - Tutone, Marco; Almerico, Anna Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a collection of original research articles in the field of computer-aided drug design. It reports the use of current and validated computational approaches applied to drug discovery as well as the development of new computational tools to identify new and more potent drugs.